2014
DOI: 10.3389/fneng.2014.00024
|View full text |Cite
|
Sign up to set email alerts
|

Acute human brain responses to intracortical microelectrode arrays: challenges and future prospects

Abstract: The emerging field of neuroprosthetics is focused on the development of new therapeutic interventions that will be able to restore some lost neural function by selective electrical stimulation or by harnessing activity recorded from populations of neurons. As more and more patients benefit from these approaches, the interest in neural interfaces has grown significantly and a new generation of penetrating microelectrode arrays are providing unprecedented access to the neurons of the central nervous system (CNS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 39 publications
1
102
0
1
Order By: Relevance
“…Once movements are sufficient to perform actions of daily life, constraint-induced movement therapy (CIMT) (Taub et al, 1999) becomes applied. of electrode positions, and the preservation of electric properties between the brain and the electrodes (eg, Fernández et al, 2014).…”
Section: Signal Modality Of Bmimentioning
confidence: 99%
“…Once movements are sufficient to perform actions of daily life, constraint-induced movement therapy (CIMT) (Taub et al, 1999) becomes applied. of electrode positions, and the preservation of electric properties between the brain and the electrodes (eg, Fernández et al, 2014).…”
Section: Signal Modality Of Bmimentioning
confidence: 99%
“…The average transverse impedance from a PMP devices (which peel testing showed good adhesion between the Parylene and metal (Figure 5) dropped slightly in magnitude at lower frequencies which are more sensitive to device failure (Fernández et al, 2014), but remained relatively constant at higher frequencies ( Figure 12A). The −90° phase of the PMP devices suggested that traces were fully insulated before bending, however, the insulation was in part compromised after the first set of bend Mechanical properties of thin-film Parylene-metal-Parylene devices Frontiers in Mechanical Engineering | www.frontiersin.org tests as indicated by the drop in phase at lower frequencies.…”
Section: Bending Fatiguementioning
confidence: 99%
“…For this reason we are using the Utah Electrode Array (UEA), which has 100 microelectrodes, each 1.5 mm long, arranged in a square grid contained in a package 4.2 mm by 4.2 mm. This array of penetrating electrodes has been designed to compromise as little cortical volume as possible, is able to selectively access individual or small groups of cortical neurons and is the only intracortical microelectrode array that has been FDA approved for long-term human studies [8]. Thus, each needle has been made as slender as possible yet retain sufficient strength to withstand the implantation procedure.…”
Section: Introductionmentioning
confidence: 99%